ANALISIS PERBEDAAN RETURN SAHAM SEBELUM DAN SESUDAH PENGUMUMAN RIGHT ISSUE - Masdalena Masdalena; Aftoni Sutanto (Universitas Ahmad Dahlan, 2014)
This research aims to determine whether there are differences in stock returns before and after the announcement of the rights issue on the Indonesia Stock Exchange 2009-2013 period. This study was conducted on 43 companies listed in the Indonesia Stock Exchange right issues in the year 2009 to 2013, with a purposive sampling method. This research used the t-test analysis test by way Paired Sample Test with the observation period (event window) there are 20 days, t-10 (10 days prior to the announcement of the rights issue) and t + 10 (10 days after the announcement of the right issue). The announcement of the test results are known to contain information because the announcement led to market tereaksinya indicated by the presence pf abnormal return that occurred and the results of t-test menunjukkan significance value 0.036<Î±0.05 to distinction stock returns 10 days prior to the stock return 10 days after the announcement of the right issue. This that information is not leaked.